La supervision de mémoire en master : l’étudiant comme principal acteur de sa réussite - Laetitia Gerard (Revue Internationale de Pédagogie de l’Enseignement Supérieur, 2011)
Research supervision is an important factor of success in master and doctoral studies. To reduce failure and attrition at this level, numerous studies have focused on the link between the quality of supervision and student success. Since supervision is a two-way relationship, the supervisor is not the sole actor in determining the student’s success. In this article we investigate the little-researched subject of the role of the student in his or her own success. Semi-directive interviews were conducted with supervisors and students in three disciplines in the social sciences and humanities in seven French universities. The results of this study show the student as the key actor in his or her success. Successful students were those who demonstrated self-direction, regardless of the real or perceived quality of supervision. Our data show that the self-directed student has two main characteristics, one being discoverying the implicit and the other being the ability to compensate real or perceived deficiencies.